Current Status of Evidence for a New Diagnosis: Food Addiction-A Literature Review - Vasiliu, Octavian (Frontiers in Psychiatry, 2022)
Food addiction is considered an important link for a better understanding of psychiatric and medical problems triggered by dysfunctions of eating behaviors, e.g., obesity, metabolic syndrome, binge eating disorder, or bulimia nervosa. At behavioral level, food addiction has high degrees of similarity with other eating disorders, a phenomenon that creates difficulties in finding specific diagnostic criteria. Food addiction has been also described as “eating addiction” or “eating dependence” by several researchers, who placed the emphasis on the behavior and not on the food itself. High-sodium foods, artificially flavored-foods, rich carbohydrate- and saturated fats-containing foods are triggers for the activation of the same neural pathways, therefore they act similarly to any drug of abuse.. Food addiction is considered a disorder based on functional negative consequences, associated distress and potential risks to both psychological well-being and physical health. A clinical scale was validated for the quantification of the eating addiction severity, namely the Yale Food Addiction Severity Scale (YFAS), constructed to match DSM IV criteria for substance dependence. Using this instrument, a high prevalence of food addiction was found in the general population, up to 20% according to a meta-analytic research. The pathogenesis of this entity is still uncertain, but reward dysfunction, impulsivity and emotion dysregulation have been considered basic mechanisms that trigger both eating dysfunctions and addictive behaviours. Genetic factors may be involved in this dependence, as modulators of higher carbohydrate and saturate fat craving. Regarding the existence of potential therapeutic solutions, lorcaserin, antiepileptic drugs, opioid antagonists, antiaddictive agents are recommended for obesity and eating disorders, and they may be intuitively used in food addiction, but clinical trials are necessary to confirm their efficacy. In conclusion, a better understanding of food addiction’s clinical profile and pathogenesis may help clinicians in finding prevention- and therapeutic-focused interventions in the near future.